2016
DOI: 10.1037/emo0000172
|View full text |Cite
|
Sign up to set email alerts
|

(De)coupling of our eyes and our mind’s eye: A dynamic process perspective on attentional bias.

Abstract: We aimed to illuminate the theorized, yet empirically elusive, connection between covert and overt attentional processes subserving attentional biases (AB). We found that covert and overt attentional processes were each expressed dynamically, fluctuating from moment-to-moment between phases of (over)engagement and phases of avoidance of threat stimuli. The key features of the temporal dynamics of covert and overt attentional processes were significantly correlated. Moreover, the real-time, dynamic expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…Future studies should also focus on the generalization of our findings to clinical populations, on the differential impact of sad and angry stimuli on depressive participants, and on the status of social emotions as potential triggers of attention biases in social anxiety. Another interesting research avenue concerns the cross-trial temporal stability of the maintenance bias we found in our socially anxious participants, in line with concerns recently raised on the dynamic expression of attention biases across time (Amir et al, 2016; Zvielli et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Future studies should also focus on the generalization of our findings to clinical populations, on the differential impact of sad and angry stimuli on depressive participants, and on the status of social emotions as potential triggers of attention biases in social anxiety. Another interesting research avenue concerns the cross-trial temporal stability of the maintenance bias we found in our socially anxious participants, in line with concerns recently raised on the dynamic expression of attention biases across time (Amir et al, 2016; Zvielli et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Tracking sheep’s head and ear movements and positions might not be ideal to measure visual attention because of the wide visual field of sheep. Therefore, using an eye tracking system might be an improvement [ 97 , 98 , 99 , 100 , 101 ]. However, it is unclear whether such a system could be calibrated to be used in species with a large visual field.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies performing this analysis have found evidence for biases in disengagement, rather than orienting, among anxious individuals (e.g., Cooper and Langton, 2006 , Koster et al, 2004 , Salemink et al, 2007 ). Others have suggested that variability in bias throughout attention tasks best capture the fluctuating patterns of attention that mark individual differences and risk ( Amir et al, 2016 , Naim et al, 2015 , Zvielli et al, 2014 , Zvielli et al, 2015 ).…”
Section: Future Directionsmentioning
confidence: 99%